2018
DOI: 10.1002/star.201800073
|View full text |Cite
|
Sign up to set email alerts
|

Cassava Bagasse as a Substrate to Produce Cyclodextrins

Abstract: Cassava bagasse (CB) is an agro-industry residue usually discarded by starch industries. In this study, CB is used as a substrate to produce cyclodextrins (CDs), due to the high carbohydrate content (62%). The influence of CB concentration (2-4%) and temperature (60-70 C) on the production of α, β, and γ-CD was verified by means of the CGTase Toruzyme enzyme. Higher CD production (8.61 mM) is observed for 4% CB at 70 C. The CB performed similar or better in the CD production and conversion rates when compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…[ 35 ] Hence, PPS seems to be very advantageous for the β‐CDs production owing to the high production level and to the low‐cost provided by this substrate. Among the raw materials previously used for β‐CDs production including cassava starch [ 21 ] and PPS, the latter was considered as the most suitable substrate to obtain a high yield of β‐CDs reaching 12.41 g L −1 . [ 36 ] This optimized production is remarkably lower than the one obtained in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] Hence, PPS seems to be very advantageous for the β‐CDs production owing to the high production level and to the low‐cost provided by this substrate. Among the raw materials previously used for β‐CDs production including cassava starch [ 21 ] and PPS, the latter was considered as the most suitable substrate to obtain a high yield of β‐CDs reaching 12.41 g L −1 . [ 36 ] This optimized production is remarkably lower than the one obtained in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19,20 ] However, potato starch is the major substrate usually used for the CDs process. For industrial applications, it is essential to reduce the CDs operating expense by using low‐cost raw materials [ 21 ] and by enhancing the production process. Therefore, the starch extraction from PP discarded by the potato processing industry could be considered as a promising trail for CDs industrial production.…”
Section: Introductionmentioning
confidence: 99%
“…Other agri-food waste extracts are those obtained from bagasse generated by the food industry and can be used in nanotechnology for the production of metal nanoparticles. Worldwide, the main bagasses generated include sugarcane bagasse and sweet sorghum bagasse [182][183][184]. Global sugarcane production is around 1.9 billion tons annually; however, this is around 570 million tons of wet bagasse, or one-half of this amount if dried [185].…”
Section: Cereal Waste Extractsmentioning
confidence: 99%
“…The proportion of CDs was dependent on the initial substrate concentration and on reaction time. [7] Ibrahim et al [8] produced CDs using different concentrations of potato starch (0.5-5.0%) as substrate. These authors found a higher conversion rate using a concentration of 1.5% starch than with a concentration of 5.0% starch.…”
Section: Production Of Cds From Wheat Starchmentioning
confidence: 99%
“…Several authors studied different starch sources as a substrate for the production of CDs [6,7] as well the CDs production with agroindustry by-products in order to reduce costs. [8] However, no reports have been found using the germinated wheat starch for this purpose. This study aims to produce of CDs (𝛼, 𝛽, and 𝛾-CD) using germinated wheat starch as substrate and evaluated the thermal stability of inclusion complex between these CDs and orange essential oil (OEO).…”
Section: Introductionmentioning
confidence: 99%